Impact of peroral cholangioscopy on the management of indeterminate biliary conditions: a multicentre prospective trial - Prat, Frederic (Frontline Gastroenterol, 2019)
BACKGROUND AND AIMS: Single-operator cholangioscopy (SOC) can help diagnose biliopancreatic conditions. The impact of SOC on patient outcome has never been specifically addressed. PATIENTS AND METHODS: Consecutive patients bearing indeterminate biliary strictures (IDBS), or primary sclerosing cholangitis (PSC) with suspected cholangiocarcinoma, were included. Patients with IDBS had at least one previous inconclusive endoscopic retrograde cholangio pancreatography (ERCP) + cytology. Primary endpoint was the difference in adequacy of management planned before and after SOC with regard to final diagnosis obtained after surgery or 24 months follow-up. DESIGN: Prospective open-label multicentre trial. RESULTS: 61 patients were included (IDBS: 48; PSC: 13); 70.5% had a benign lesion (IDBS 66.7%, PSC 84.6%). The management adequacy rate was significantly higher after SOC than before SOC overall (p<10(–5)), in IDBS (p<0.001) and PSC (p<0.05) patients. SOC induced changes in the management of the majority of patients in all groups (60.3%). The overall sensitivity of combined visual impression and biopsy ranged from 52% to 63.6% depending on investigator or independent expert rating (κ 0.92–0.96), whereas specificity, positive and negative predictive values of SOC were, respectively, 100%, 100% and 83.6%. Patient management observed at the end of follow-up was consistent with that anticipated after SOC in 88.5% overall. CONCLUSION: Despite a moderate sensitivity for the diagnosis of malignancy, SOC has a dramatic impact on the management of patients with IDBS and PSC with suspected carcinoma. Cholangioscopy might be implemented in the workup of selected patients with challenging diagnosis, when a significant impact on outcome (essentially resection vs conservative management) is to be expected.